Avaliação da ecoeficiência e da pegada hídrica do processamento da carne de frango no Centro-Oeste do Brasil - Marques, Thamiris Linhares (Universidade Federal de São Carlos, 2019)
Water is an indispensable natural resource for life on Earth and it is used indirectly or directly at all productive activities. Therefore, attention to the impacts of water use is a relevant topic for the sustainable production. Brazil is one the world´s largest producer of chicken meat, which can promote several environmental impacts, including water resources. Thus, the objective of this master’s dissertation was to perform a Water Footprint Assessment and ecoefficiency assessment of the processing of poultry meat in Brazil. For the water footprint, it was used the ISO14046:2014 standard and the impact assessment methods chosen were: ReCiPe Midpoint (H) for freshwater eutrophication category, USEtox for ecotoxicity and carcinogenic and non-carcinogenic human toxicity categories, and the Available Water Remaining (AWARE) method was adopted for the water scarcity category. The product system defined was modeled from a cradle-to-gate perspective, from obtaining live chicken to slaughter, and processing meat and co-products generation. In addition, eco-efficiency was measured for each of the processes mapped based on ISO 14045:2012 guidelines. The results showed that chicken farm is a process with greater generation of water impacts (up to 98,7%) when compared to the industrial manufacturing activities. However, knowing that time is a key issue for any manufacturing process, the water footprint associated with poultry fattening and manufacturing processing time were evaluated, showing that the manufacturing was the environmental hotspot at this time. At manufacture level, chilling was the most damaging process to water resources (up to 99,7%) per unit of time. The most ecoefficient process was defeathiring and the least one was the bleeding process. Finally, it can be concluded that there was a change in the environmental hotspot analysis of the study when performing the ecoefficiency assessment vs. Water Footprint approach. Therefore, adopting or not of both of these two approaches is critical for proposing improvements and creating new scenarios looking for alternatives for improving environmental performance under the life cycle of products.
Ecoefficiency and water footprint assessment of the processing of chicken meat in the Central West of Brazil
Keywords: Gestão do ciclo de vida; Avaliação de impacto; Processos de manufatura; Agroindústria; Avicultura; Abatedouro; Life cycle management; Impact assessment; Manufacturing process; Agribusiness; Chicken farming; Slaughterhouse; ENGENHARIAS::ENGENHARIA DE PRODUCAO